2011
DOI: 10.1182/blood-2011-06-275610
|View full text |Cite
|
Sign up to set email alerts
|

CD38 and chronic lymphocytic leukemia: a decade later

Abstract: This review highlights a decade of investigations into the role of CD38 in CLL. CD38 is accepted as a dependable marker of unfavorable prognosis and as an indicator of activation and proliferation of cells when tested. Leukemic clones with higher numbers of CD38 ؉ cells are more responsive to BCR signaling and are characterized by enhanced migration. In vitro activation through CD38 drives CLL proliferation and chemotaxis via a signaling pathway that includes ZAP-70 and ERK1/2. Finally, CD38 is under a polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
160
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(166 citation statements)
references
References 104 publications
2
160
0
2
Order By: Relevance
“…CD38 is a transmembrane glycoprotein with ectoenzymatic activity in the catabolism of extracellular nucleotides [11][12][13][14][15]. Other functions include receptor-mediated adhesion by interacting with CD31 or hyaluronic acid, regulation of migration, and signaling events [16].…”
Section: Interference With Blood Compatibility Testingmentioning
confidence: 99%
“…CD38 is a transmembrane glycoprotein with ectoenzymatic activity in the catabolism of extracellular nucleotides [11][12][13][14][15]. Other functions include receptor-mediated adhesion by interacting with CD31 or hyaluronic acid, regulation of migration, and signaling events [16].…”
Section: Interference With Blood Compatibility Testingmentioning
confidence: 99%
“…Furthermore, long-lived and/or MMinitiating cells from which MM plasma cells are derived are CD38 ++(high) CD19 -(negative) plasma cells that are either CD138 + or CD138 - [22,23], suggesting that these may in turn identify MM stem cells that are relatively resistant to therapy. Interestingly, CD38 expression in CLL is associated with a more aggressive clinical behaviour, as CD38+ patients have a shorter progression-free and overall survival [6]. In vitro studies have shown that interaction between CD38 and CD31 promotes the proliferation and survival of CLL cells both directly and through up-regulation of CD100 [24], which interacts with plexin-B1 on stromal cells and some subsets of T cells [25].…”
Section: Rationale For Targeting Cd38 For Cancer Immunotherapymentioning
confidence: 99%
“…Functional CD38 appears as a dimer or a multimer [3] on the cytoplasmic side of the membrane, where its catalytic site is defined [4]. As a receptor, CD38 is preferentially localized in lipid rafts, microdomains of plasma membrane and is in close contact with the BCR complex and with other molecules (i.e., CXCR4) regulating signaling, homing, adhesion and migration [5,6]. Lipid raft localization and association with signaling complexes are prerequisites for signals mediated through CD38 to phosphorylate ERK1/2 and activate NF-kB [7,8].…”
mentioning
confidence: 99%
“…It is now generally accepted that CD38 + patients will have a shorter progression-free interval, require earlier and more frequent treatments, and ultimately die sooner. It remains undeniable that CD38 marks the majority of clinically more aggressive leukemic clones requiring treatment (19).…”
Section: Cd38 In Chronic Lymphocytic Leukemiamentioning
confidence: 99%